Evidence of Bacterial Biofilms in Human Chronic Sinusitis - Israr Ud Din, Shaista Alam, Muhammad Hafeez, Mansoor Alam, Shabir Ahmed Orakzai, Saman Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The reason of this study design is to analyze the presence of bacterial biofilm on the sinus mucosal surface of humans with the presence of stubborn chronic sinusitis. Place and duration of study: The study is conducted in Khyber Teaching Hospital ENT Peshawar and the duration of study is March 2022 to August 2022. Material and Method: We have evaluated small Sinonasal samples from 20 numbers of patients having previous history of sinus surgery or surgical intervention. No courses of antibiotic and endoscopic sinus surgery work best for all the number of samples. By the use of cutting instrument we have seen the ethmoid sinus mucosal specimens and maxillary specimens. Scanning and microscopic evaluation techniques are used to detect patients with continuous manifestations of chronic sinusitis even with prior medical and surgical intervention. Results: Physical presence of microbial cluster of pseudomonas aeroginosa, a gram negative bacteria validate the existence of microbes in the sinus mucosa of patients. The existence of this microbial cluster may provide the evaluation of stubborn nature of some appearance of chronic sinusitis. Conclusion: Spire shaped cluster of microbes are the structural indication of the presence of microbial biofilms in a patient with chronic sinusitis.Not only antibiotics but the combination of peroperative antibiotics and surgical intervention treatment therapy is recommended in such kind of chronic infections. Keywords: Gram negative bacteria, sinonasal epithelium, electron microscopy